VENDIMIA research center in the construction of collective knowledge. A historical look (2006-2014) - Soto Arango, Diana Elvira; Lima Jardilino, José Rubens; Mora García, José Pascual (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objetive: This paper characterizes the historiographic contributions to bibliometric research in the history of education based on the study of the VENDIMIA research center. Originality/Contribution: we show how the dialogue between several Colombian research groups and Ibero-American groups has contributed to the construction of a collective knowledge influencing socio-educational transformation and contributing to Latin American integration from the academy. Method: This is a documentary and historiographic research. It is based on research networks and the method of the social history of education developed by the Society for the History of Latin American Education, SHELA. Strategies, Data Collection: The study period begins in 2006, creation and first group meeting, and covers until 2014 when the last event and meeting of the center takes place. Therefore, the sources consisted of: national and institutional regulations together with those of the Vendimia network, minutes documents, research projects, publications in books and bulletins, event reviews, research lines, pedagogical experiences and opinion interviews. Conclusions: This network experience with research groups consolidated a practice that had an impact on the academic program of the Doctorate in Educational Sciences of RUDECOLOMBIA, by promoting a central line of research that strengthened the theses and postdoctoral projects.